Exposure to carbon black nanoparticles during pregnancy persistently damages the cerebrovascular function in female mice. (15th June 2019) - Zhang, Yujia; Tu, Baijie; Jiang, Xuejun; Xu, Ge; Liu, Xuemei; Tang, Qianghu; Bai, Lulu; Meng, Pan; Zhang, Longbin; Qin, Xia; Zou, Zhen; Chen, Chengzhi
Graphical abstract: Abstract: Maternal exposure to carbon black nanoparticles (CBNPs) during pregnancy have been well documented to induce harmful outcomes of offspring on brain function. However, it remains largely unknown whether females exposed to CBNPs during sensitive period of pregnancy can cause the neurotoxic effects on their own body after parturition. In this study, our results showed that pregnancy CBNPs exposure induced the persistent pathological changes in the cerebral cortex tissues and impaired cerebrovascular function of mice manifested by significant alterations of endothelin-1, endothelial nitric oxide synthase, vascular endothelial growth factor-A and ATP-binding cassette transporter G1. Intriguingly, we observed that these deleterious effects on brain and cerebrovascular functions in mice could persist for 49 days after delivery of pups. By using in vitro human umbilical vein endothelial cells, we further verified the potential vascular dysfunction after CBNPs exposure. In summary, our results provide the first evidence that pregnancy CBNPs exposure-induced brain pathological changes and cerebrovascular dysfunction can persist for a relative long time. These finding suggest exposure to CBNPs during sensitive stages of pregnancy may not only show the harmful effects on offspring neurodevelopment, but also result in the irreversible brain damage on mother body.